Korelacijska analiza primijenjena na ozljede na radu i dane bolovanja - Tevčić, Marina (Array, 2021)
The procedure of correlation analysis is based on the determination of direction and strength indicators between the observed phenomena or variables. Correlation analysis, in addition to determining the numerical indicator (linear correlation coefficient), includes a graphical representation (scatter diagram, scatter plot) from which it is seen whether or not there is a connection of the observed phenomena and if so, what is the shape, direction and strength of this connection. The paper also describes the procedure for conducting a test of the significance of the calculated linear correlation coefficient. Based on statistical data, the relationship between the number of sick days and the number of injuries at work in the Republic of Croatia and in Karlovac County in the period from 2012 to 2019 was analyzed. The conducted correlation analyzes indicate a strong correlation between the number of used sick days and the number of injuries at work (total number of injuries at work and injuries at work) both in the Republic of Croatia globally and in Karlovac County locally. On the other hand, it has been shown that there is a weak correlation between the number of injuries on the way to / from the place of work and the total number of injuries at work, both in Karlovac County and at the level of the Republic of Croatia.